Designing strategy for the globalisation of innovation: perspectives for foreign electric vehicle manufacturers in China. (2016) - Chen, Bo; Midler, Christophe
Despite efforts to deploy electric vehicles, sales from western carmakers in China remain insignificant compared with domestic carmakers. Although literature on the Chinese market, on innovation and on strategy for foreign multinational enterprises in China is abundant, it lacks specific research on strategic perspectives for foreign players experiencing the country's complex and uncertain context. To tackle this empirical question, the paper proposes a novel analytical method through bridging the literature on strategy, innovation and the Chinese EV market. A 'strategic opportunities space' is developed to explore potential strategic paths. The application of this method to the Chinese EV case leads to defining 12 best-fit scenarios for western car manufacturers. Our findings indicate that among the selected solutions, the still untapped low-cost approach to electric vehicles in China's lower tier cities brings the highest value to foreign carmakers, while potentially being a favourable candidate for reverse innovation.